Penentuan PENENTUAN ZONA AGROEKOLOGI UNTUK ARAHAN KOMODITAS PERTANIAN HORTIKULTURA KABUPATEN AGAM DENGAN MENGGUNAKAN BAHASA PEMOGRAMAN PYTHON - Habib, M. Ilham (JURNAL BUANA, 2026)
FAO introduced the concept of Agro-Ecological Zones around 1978 to assist in integrated agricultural land planning and management. Therefore, this study aims to analyze the Agro-Ecological Zones of Agam Regency as a guideline for agricultural commodities, particularly horticultural commodities. This study utilizing Python programming. The analysis employs IF Else logic in Python to match the requirements of the Agro-Ecological Zones with the physical conditions of the region. The results of the analysis show that the main zone is dominated by Zone VII, which has slopes of less than 8%, covering an area of 81,146.44, where this zone is very suitable for horticultural crops due to its flat slopes. In the sub Agro-Ecological Zones, it is dominated by Sub-Zone D (dry land), covering 170,385.44, which has good, fast, and somewhat impeded drainage. Thus, it can be seen that the majority of the area in Agam Regency is suitable for crops that thrive on dry land, such as horticultural crops.